2023
DOI: 10.1364/oe.484369
|View full text |Cite
|
Sign up to set email alerts
|

Phononically shielded photonic-crystal mirror membranes for cavity quantum optomechanics

Abstract: We present a highly reflective, sub-wavelength-thick membrane resonator featuring high mechanical quality factor and discuss its applicability for cavity optomechanics. The 88.5 nm thin stoichiometric silicon-nitride membrane, designed and fabricated to combine 2D-photonic and phononic crystal patterns, reaches reflectivities up to 99.89 % and a mechanical quality factor of 2.9 × 107 at room temperature. We construct a Fabry-Perot-type optical cavity, with the membrane forming one terminating mirror. The optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Suspended PhCs combine excellent mechanical and optical properties due to their small weight, low mechanical dissipation, and engineerable optical reflectivity [24][25][26][27][28][29]. As a consequence, PhC slabs have been considered in theoretical proposals for optomechanical systems [30,31] and have been used in various optomechanical experiments already [28,[32][33][34]. Recently, it was shown that a cavity optomechanical system formed between two suspended PhC slabs realizes a Fabry-Perot-type optical BIC [5,8], exhibiting a quality factor only limited by intrinsic loss in the material [17,[35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Suspended PhCs combine excellent mechanical and optical properties due to their small weight, low mechanical dissipation, and engineerable optical reflectivity [24][25][26][27][28][29]. As a consequence, PhC slabs have been considered in theoretical proposals for optomechanical systems [30,31] and have been used in various optomechanical experiments already [28,[32][33][34]. Recently, it was shown that a cavity optomechanical system formed between two suspended PhC slabs realizes a Fabry-Perot-type optical BIC [5,8], exhibiting a quality factor only limited by intrinsic loss in the material [17,[35][36][37].…”
Section: Introductionmentioning
confidence: 99%